Studi Living: Persepsi Masyarakat Terhadap Tradisi Bacaan Shalat Tolak Bala - Hasibuan, Elida Marwiyah; Hasiah, Hasiah; Siregar, Sawaluddin (Jurnal El-Thawalib, 2024)
This article examines the perceptions of the people of Hutaraja Lamo Village, Sosa District, Padang Lawas Regency towards reading the prayer to reject reinforcements. This type of research is field research with a qualitative approach. The primary data sources in this article are religious leaders, traditional leaders, village heads, Naoso Nauli Bulung and the Hutaraja Lamo village community. While the secondary data comes from books, journal articles related to this article. for data collection techniques using observation, interviews and documentation, then analyzed using data analysis techniques is descriptive research. The results of this study indicate that the people of Hutaraja Lamo village, Sosa sub-district, Padang Lawas district believe that the community's understanding of the recitation of the prayer to reject reinforcements is selected verses (al-ikhlas, an-nas and al-falaq). As well as reciting three times after al-Fatihah, totaling four cycles, one greeting and having a bayati rhythm. The public's understanding of the recitation of the prayer against reinforcements may be carried out and there is no compulsion to carry it out. When there are conditions such as being overwritten by a disaster or a disease that does not go away. Then it is permissible to carry out the recitation of the prayer to repel reinforcements with the aim of asking forgiveness from Allah SWT. So by holding the recitation of the prayer to repel reinforcements, this is done with the intention because of Allah Ta'ala and surrendering to Him all illnesses will disappear forever. As for the people's reasons for reading the prayer to reject reinforcements, it must be done with confidence and surrender to Allah. The people also say that after reading the prayer to repel reinforcements, there is a change in the people who are sick, and all the calamities that have befallen us all will not come again. The reason for the community to carry out the recitation of the prayer to reject reinforcements must be with confidence and surrender to Allah.